Evaluation Of Breast Lesions By Fine Needle Aspiration Cytology And Correlation With Histopathological Examination (Indian Journal of Applied-Basic Medical Sciences, 2021)
INTRODUCTION: Breast cancer is the most common cancer in worldwide between age of  20-59 years females. It is responsible for 15% of total deaths due to cancers. FNAC is one of  the important components of ‘triple approach’, which has been widely accepted for the  preoperative diagnosis of breast lesions.  AIM: To establish utility and effectiveness in diagnosis of breast lesion by FNAC and find the  incidence of breast cancer in palpable lump in different age groups.  MATERIAL AND METHODS: In this study100 cases of breast lump referred by the Surgery  Department of LG Hospital was included in study period fromAugust2016toOctober2018. RESULT: Out of the 100 cases, in 99 cases the aspirates were adequate for interpretation. Out  of 100, 90cases underwent a biopsy and could be correlated histopathologically. According to  NHSBSP, there was 1 case in C1 category,64 cases in C2 category, 3 cases in C3 category, 2  cases in C4 category and 30casesin C5 category.  CONCLUSION: The present study categorized by NHSBSP criteria conclude 100%  confirmation in C4 and C5 category in age group above 40 years showing malignancy by  histopathology. The overall sensitivity in the study was 83.33%, specificity was 100%, positive  predictive value in disease was 100% and the false negative percentage was 16.66%. FNAC is  an accurate and reliable preoperative diagnostic tool for breast lesions.
Keywords: Breast Lesions; Aspiration Cytology; histopathological; correlation